Cross‐Sectional Analysis of Spatial Working Memory Development in Children with Histories of Heavy Prenatal Alcohol Exposure. (6th January 2021) - Moore, Eileen M.; Glass, Leila; Infante, M. Alejandra; Coles, Claire D.; Kable, Julie A.; Jones, Kenneth L.; Riley, Edward P.; Mattson, Sarah N.; ,
Abstract : Background: In children with prenatal alcohol exposure, spatial working memory is affected and brain regions important for spatial working memory performance exhibit atypical neurodevelopment. We therefore hypothesized that children with prenatal alcohol exposure may also have atypical development of spatial working memory ability. Methods: We examined the relation between spatial working memory and age using a cross‐sectional developmental trajectory approach in youth with and without histories of heavy prenatal alcohol exposure. The Cambridge Neuropsychological Test Automated Battery Spatial Working Memory subtest was administered to children 5.0 to 16.9 years old. Results: While the controls and children with prenatal alcohol exposure showed similar performance at younger ages, larger group differences were observed in older children. This effect was replicated in a separate sample. Conclusions: The atypical brain development that has previously been reported in children with heavy prenatal alcohol exposure may have clinically relevant implications for cognitive development; however, longitudinal cognitive analyses are needed. Abstract : While young children with heavy prenatal alcohol exposure make equivalent amounts of errors and utilize a similar strategy as controls on the CANTAB Spatial Working Memory Test, by age 16 there is nearly a whole standard deviation difference between the groups on these two performance measures. This cross‐sectional data suggests that children with prenatal alcohol exposure develop the cognitive abilities necessary for spatial working memory at a slower rate than controls.